PENGARUH PERSEPSI HARGA DAN KUALITAS LAYANAN TERHADAP KEPUASAN PELANGGAN (Studi Pada Pelanggan Hotel Graha Agung MAJT Semarang) (Students' Journal of Economic and Management, 2015)
This studyaimed toanalyze the influence ofperceptionsof price and qualityof serviceto customer satisfactioninthe SupremeMAJTGrahaHotelSemarang. The amound of visitors sampled totaling 100 customers. The objectof research used inthis studyisthe SupremeMAJTcustomerGrahaHotelSemarang. The sampling techniqueusedinthis research ispurposivesampling.The results ofthe study are priceperception variable noteffectto variablecustomersatisfaction and servicequalityvariableshas positiveeffecttovariablesof customer satisfaction. Keywords: Perceptions ofPrice, Quality of Service, andCustomerSatisfaction.